2019
DOI: 10.1088/1757-899x/698/4/044036
|View full text |Cite
|
Sign up to set email alerts
|

A study of hailstorms in the South of Western Siberia

Abstract: The paper presents the mapped spatial distribution of the maximum hail days in the period 1966–2016 and the number of hailfall with different diameters and hail frequency from 2015 to 2018. The territories most affected by hail are identified, the key factor is orography. Hail with an annual frequency of occurrence is observed mainly in regions with an altitudes of more than 300 masl which influenced by the southern mountains of Siberia. The characteristics of convective clouds (height and cloud top temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Punge et al developed a hail event dataset for Europe based on the OT algorithm by using MSG-SEVIRI data [5,19]. In recent years, many studies have also found that hailstorms can be accurately captured by combing satellite and radar, improving the effectiveness of statistical analysis and artificial hail suppression [33][34][35][36][37][38][39][40][41]. Auer et al proposed a hail recognition technique through the combined use of radar reflectivity and cloud-top temperatures (CTT) to forecast hail [33].…”
Section: Introductionmentioning
confidence: 99%
“…Punge et al developed a hail event dataset for Europe based on the OT algorithm by using MSG-SEVIRI data [5,19]. In recent years, many studies have also found that hailstorms can be accurately captured by combing satellite and radar, improving the effectiveness of statistical analysis and artificial hail suppression [33][34][35][36][37][38][39][40][41]. Auer et al proposed a hail recognition technique through the combined use of radar reflectivity and cloud-top temperatures (CTT) to forecast hail [33].…”
Section: Introductionmentioning
confidence: 99%